Diagnosis, etiology, and management strategies of open bite malocclusions - Farran, Waleed H.; Alhazmi, Ammar K.; Bahshan, Ibrahim A.; Alhabib, Batool N.; Alsultan, Ameen A.; Alaraj, Denah I.; Albash, Abdullah F.; Alshahrani, Eilaf A.; Baflah, Mohammed A.; Almalallah, Fatimah Y. (International Journal Of Community Medicine And Public Health, 2023)
Open bite malocclusion is a condition where the upper and lower incisors do not overlap vertically. It involves factors like structure, dental issues and functional challenges. This review offers an overview of diagnosing, understanding the causes and managing bite malocclusions. The condition is noticeable by the gap between incisors, difficulties in biting and speech and habits like tongue thrusting. In children thumb sucking is often associated with this issue underscoring the importance of intervention. Diagnosis relies on assessments, cephalometric analysis and categorization based on dental or skeletal elements. The causes can be attributed to factors, environmental influences or behavioral habits. Various management strategies are available with treatments playing a role using methods like fixed appliances clear aligners, and innovative temporary anchorage devices (TADs). Surgical interventions such as surgery address discrepancies when necessary. Considering that open bites are age conditions, behavioral modifications along with intervention using orthopedic appliances are crucial for effective treatment. Advanced diagnostic tools like cone beam computed tomography (CBCT) contribute to treatment planning. The retention phase ensures stability of results while patient cooperation remains essential throughout the process. Collaboration between orthodontist’s maxillofacial surgeons and other specialists is vital for care. The field of orthodontics is continuously advancing and with research we can expect improvements in our understanding and treatment of open bite malocclusions.